Effectuation - Maamari, Bassem E. (2017)
Although much research in knowledge management has linked tacit knowledge with its two dimensions, the cognitive and technical, with innovation performance in firms, but exploring a new dimension for tacit knowledge is still a core tenet. In this study, we propose effectuation as a new dimension of tacit knowledge and empirically test a quantifiable model with 331 respondents in the service industry in Lebanon. So our objective is to discover whether this new dimension can enhance the potential of tacit knowledge in affecting innovation performance and thus can very likely be considered a development to the theory of tacit knowledge.